Analisis Konsep Body Positivity Melaui Resepsi Audiens Dalam Kampanye #Respectmybody Pada Instagram (Studi Kasus Kampanye Brand Somethinc) - Magafira, Nurul Istian; Purwanti, Silviana; Rohma, Ainun Ni’ Matu; Alfando WS, Johantan (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research uses a qualitative approach with Stuart Hall's reception analysis method. Where in the method divides the audience into 3 categories , namely Dominant Hegemonic Position, Negotiated Position, and Oppositional Position. The data analysis technique used in this research is the Miles and Huberman interactive model data analysis. The results of this study show that audiences have the ability to digest and convert media messages into definitions of life choices and self-identity. Audiences are given the option to choose which media to consume according to their preferences. The informants were found to be divided into three positions where two informants were in the Dominant Hegemonic Position, which means that they agree with the #Respectmybody campaign that the message and the initial objectives of Brand Somethinc are well conveyed to the informants. The other two are in the negotiation position where the audience generally accepts the dominant ideology but they will make some exceptions in its application according to cultural rules to their own thoughts. And one is in the opposition position where the audience rejects the intended message of the media and replaces it with their own way of thinking about the topic conveyed by the media.